Do ‘green’ employment effects vary across industries? Implications for green growth - Lie, Christine Mee (Oslo, 2016)
"This article investigates the impact of green innovation on employment growth, employing firm-level survey data from South Korea. We focus especially on the industry-dimension, investigating whether displacement or compensation effects vary across industries and according to subtypes of green process innovations. Results demonstrate that both green and non-green product innovations are associated with significant employment increases: a 1% increase in sales growth from new products is associated with a less than 1% increase in employment. Finally results are found to vary across industries, especially when simultaneously accounting for subtypes of green process innovations."